2015
DOI: 10.1117/12.2177219
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear synthetic aperture radar imaging using a harmonic radar

Abstract: This paper presents synthetic aperture radar (SAR) images of linear and nonlinear targets. Data are collected using a linear/nonlinear step frequency radar. We show that it is indeed possible to produce SAR images using a nonlinear radar. Furthermore, it is shown that the nonlinear radar is able to reduce linear clutter by at least 80 dB compared to a linear radar. The nonlinear SAR images also show the system's ability to detect small electronic devices in the presence of large linear clutter. The system pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…This distance offset d 0 is a correction that accounts for the non-negligible delay of signals propagating within the radar, which every signal will experience just before transmission from the antenna and just after capture by the antenna. If d 0 is ignored, the calculation given by (8) will result in a consistent over-estimate of the true value of d because the phase of V rec relative to V trans will always contain such a delay. For short standoff distances ( For a particular nonlinear radar, the distance d 0 may be extracted by (a) measuring delay through each of the cables, connectors, and components in the transmit and receive paths, adding them up, and dividing by 2, or (b) placing a nonlinear target directly in front of the antenna (d = 0) and calculating range-to-target using (9).…”
Section: Wireless Experimentsmentioning
confidence: 96%
See 2 more Smart Citations
“…This distance offset d 0 is a correction that accounts for the non-negligible delay of signals propagating within the radar, which every signal will experience just before transmission from the antenna and just after capture by the antenna. If d 0 is ignored, the calculation given by (8) will result in a consistent over-estimate of the true value of d because the phase of V rec relative to V trans will always contain such a delay. For short standoff distances ( For a particular nonlinear radar, the distance d 0 may be extracted by (a) measuring delay through each of the cables, connectors, and components in the transmit and receive paths, adding them up, and dividing by 2, or (b) placing a nonlinear target directly in front of the antenna (d = 0) and calculating range-to-target using (9).…”
Section: Wireless Experimentsmentioning
confidence: 96%
“…Recently, the authors demonstrated over-the-air detection and ranging of nonlinear targets using transmit waveforms that were chirped [6] or stepped [7] across an ultra-wide bandwidth. Selecting the stepped-frequency transmit waveform, the authors generated images of nonlinear targets using a synthetic aperture [8] and demonstrated moving target indication of nonlinear targets [9]. Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the nth harmonic received at the radar, f r , has a bandwidth of nB centered around n f 0 , due to the linear multiplication of the fundamental frequency band. For a harmonic radar operating at the nth harmonic, the maximum unambiguous range to the target, R max , and the down range resolution,∆R, are given by, respectively [52] …”
Section: Unambiguous Range and Range Resolutionmentioning
confidence: 99%
“…One of the less common nonlinear mechanisms is passive intermodulation (PIM) distortion, which occurs in antennas [1,2], cables, connectors [2][3][4], metal-to-metal junctions [5,6], and various components [7,8]. A recent development has led to the exploitation of nonlinearities in electronic circuits to detect and track nonlinear targets [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%